2015
DOI: 10.15287/afr.2015.360
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear microsatellite markers for population genetic studies in sugar maple (Acer saccharum Marsh.)

Abstract: Abstract. A set of seven new nuclear microsatellite markers (nSSRs) was developed for sugar maple (Acer saccharum Marsh.) using paired-end Illumina sequencing. Out of 96 primers screened in a panel of six unrelated individuals, seven markers amplified polymorphic products. The utility of these markers, in addition to six already published microsatellites, for genetic variation and gene flow studies was assessed. Out of the seven newly developed markers, three amplified multiple fragments and were interpreted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Our results were in the range reported by Khodwekar et al. () ( H E = 0.822), by Graignic et al. () ( H E = 0.689), and other species such as Acer mono Maxim.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results were in the range reported by Khodwekar et al. () ( H E = 0.822), by Graignic et al. () ( H E = 0.689), and other species such as Acer mono Maxim.…”
Section: Discussionsupporting
confidence: 89%
“…() revealed a high level of genetic diversity in sugar maple populations (see Table ). Only two studies using microsatellite markers on natural population of sugar maple (Graignic et al., ; Khodwekar, Staton, Coggeshall, Carlson, & Gailing, ) were available for comparison with our results. Our results were in the range reported by Khodwekar et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Khodwekar et al. () reported that 78–82% of gene flow in a sugar maple stand originates from outside of the stand. These authors also established the absence of fine‐scale spatial genetic structure (SGS), suggesting effective dispersal of both seeds and pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pollen gene flow is very important in sugar maple populations (e.g., Khodwekar et al. ). Low levels of genetic differentiation have been reported for sugar maple stands at local ( F ST ≤0.017) and regional scales ( F ST ≤0.049; Ontario to Nova Scotia, Canada; Young et al.…”
Section: Discussionmentioning
confidence: 99%